Pharmacological Treatment of Autism Spectrum Disorder: A Systematic Review of Treatment Guidelines - Tomiyama, Sota; Yoshida, Kazunari; Tani, Hideaki; Uchida, Hiroyuki (Pharmacopsychiatry, 2025)
Currently available systematic reviews on the pharmacological treatment of autism spectrum disorder (ASD) do not encompass all the evidence, as they exclude guidelines issued by national or local authorities that are not indexed in search engines such as PubMed.A systematic literature search was conducted to identify clinical guidelines on this topic using EMBASE, Medline, and PsycINFO. A manual search was also performed to identify guidelines by national or local authorities not included in the aforementioned databases.Thirty-eight guidelines were identified through manual search, including 27 items through search engines, 2 general guidelines, and 9 government agency guidelines. Many guidelines recommended risperidone (N=16) for the characteristic behaviors of ASD core features. For attention-deficit/hyperactivity disorder (ADHD) features, methylphenidate was most frequently recommended (N=23) for both inattention (N=6) and hyperactivity/impulsivity (N=16). Risperidone was also frequently recommended for maladaptive behaviors (N=33).A comprehensive literature search identified treatment guidelines for ASD issued by local or national administrative bodies that were not captured through search engines alone. There was some consensus among the guidelines on the use of psychotropics in alleviating specific features of ASD. However, physicians need to be aware of the lack of high-quality evidence supporting these recommendations.
Keywords: autistic disorders; risperidone (risperdal); attention-deficit/hyperactivity disorder(ADHD)